Nostalgia, Nilai, dan Kepercayaan Pengaruhnya Terhadap Kepuasan Wisatawan - Ruspitasari, Widi Dewi (Akutansi Bisnis & Manajemen ( ABM ), 2016)
The development of the tourism sector in Indonesia is growing very good, it’s offset by the natural resources owned by Indonesia is diverse. The most important strength of the tourism industry in Indonesia comes from natural resources and cultural diversity which is owned by Indonesia. Every place of tourism in Indonesia always has a variety cultures from one others. The purpose of this study to determine the effect of nostalgia, values, and beliefs has influence to satisfaction of tourists. The number of samples in this research were 50 tourists who visit Batu, using PLS analysis to test every variables. The results showed that nostalgia has no effect to travelers trust. While nostalgia has influence to the tourists value. Values and beliefs has influence to the satisfaction of tourists who visit Batu.